Moving Beyond DNA Sequence to Improve Plant Stress Responses - Saeed, Faisal; Chaudhry, Usman Khalid; Bakhsh, Allah; Raza, Ali; Saeed, Yasir; Bohra, Abhishek; Varshney, Rajeev K. (Frontiers in Genetics, 2022)
Plants offer a habitat for a range of interactions to occur among different stress factors. Epigenetics has become the most promising functional genomics tool, with huge potential for improving plant adaptation to biotic and abiotic stresses. Advances in plant molecular biology have dramatically changed our understanding of the molecular mechanisms that control these interactions, and plant epigenetics has attracted great interest in this context. Accumulating literature substantiates the crucial role of epigenetics in the diversity of plant responses that can be harnessed to accelerate the progress of crop improvement. However, harnessing epigenetics to its full potential will require a thorough understanding of the epigenetic modifications and assessing the functional relevance of these variants. The modern technologies of profiling and engineering plants at genome-wide scale provide new horizons to elucidate how epigenetic modifications occur in plants in response to stress conditions. This review summarizes recent progress on understanding the epigenetic regulation of plant stress responses, methods to detect genome wide epigenetic modifications and disentangling their contributions to plant phenotypes from other sources of variations. Key epigenetic mechanisms underlying stress memory are highlighted. Linking plant response with the patterns of epigenetic variations would help devise breeding strategies for improving crop performance under stressed scenarios.